SOIL LAYER CUT OFF BY THE AGGREGATE FOR REMOVING THE TOPSOIL FROM THE ROAD SUBLAYER: DETERMINATION OF THE CHAIN SPEED AND SIZES - V. A. Nikolaev (Вестник СибАДИ, 2020)
Introduction. For the durable road at the minimum necessary cost of its construction the topsoil should be removed without affecting the ground. The problem of cheaper road construction without reducing the quality can be solved by creating an aggregate for the sublayer’s formation. The aggregate removes the topsoil from half of the road sublayer and one of the ditch. The buckets of the moving aggregate cut off the soil layer from below and from one side. Therefore, each bucket is mounted by the bottom blade, the right blade and the console blade, partially cutting the topsoil from below for the passage of the next bucket. The blade of the lower knife with the 10 degrees’ angle to the plank of the bucket; the blade of the right knife and the blade of the console knife – with the 45 degrees’ angle towards the direction of the bucket moving.Materials and methods. To determine the speed of chains and the size of the soil layer the author carried out the bucket kinematics’ analysis and considered mathematical transformations. For checking the received parameters, the paper demonstrated the turn of the bucket on the leading 90 degrees’ lower drive. The author revealed the scheme of forces acting on the ground, located in the bucket, when it turned on the leading lower drive. Based on the system’s transformations of two equations and the inequality, the research established the inadmissibility of the bucket’s phasing out when it turned on the leading lower drive.Results. As a result, by using the developed method of determining parameters, based on the accepted raw data, the author calculated the speed of the chains, to which the buckets were attached, and the width of the soil, cut off by the bucket. After substitution of the received parameters in the inequality the author established that the ground would not fall out of the bucket by turning under such parameters of the bucket and of the leading lower drive.Discussion and conclusions. As a result, the author obtains the geometric parameters from the structural layout of the aggregate for removing the topsoil from the road sublayer. Based on the analysis of the kinematics of the interaction of the bucket with the ground, the paper reveals the speed of the chains, to which the buckets are attached and the width of the soil layer cut off by the bucket. Analysis of the forces acting on the ground and locating in the bucket at the moment of the bucket turn on the leading lower drive shows the rationality of the accepted and calculated parameters. The author determines the energy costs of cutting the ground with the buckets of the aggregate for removing the topsoil from the road sublayer.Financial transparency: the author has no financial interest in the presented materials or methods. There is no conflict of interest.